Effect of kinetics on the photocatalytic degradation of acetaminophen and the distribution of major intermediate with anatase-Ag synthesized by sol gel under visible irradiation - Aguilar, Claudia A.; de la Cruz, Alberto; Montalvo, Carlos; Ruiz-Marín, Alejandro; Oros-Ruiz, Socorro; Figueroa-Ramírez, Sandra J.; Abatal, Mohamed; Anguebes, Francisco; Córdova-Quiroz, Victor (Frontiers in Environmental Science, 2022)
The degradation of acetaminophen (ACET) was studied with TiO2-Ag catalysts, whose predominant crystalline phase was anatase synthesized by the Sol-Gel method and doped by photo-deposition under UV radiation with silver particles. The catalyst was characterized by energy dispersive X-ray fluorescence (EDXRF) and X-ray diffraction (XRD). The acetaminophen degradation was determined by high performance liquid chromatography (HPLC) and total organic carbon (TOC). The reaction behavior was studied under the Langmiur-Hinshelwood (LH-HW) kinetic model and in a TOC-based model. With the experimental data, mass balances were performed to introduce the constants (reaction and adsorption kinetics) to the LH-HW equation. With the analysis of the generation and consumption behavior of the organic intermediate compounds (OI), coupled differential equations were generated; which express the degradation and formation-consumption behavior. The kinetic constants were obtained by nonlinear regression using the Levenberg-Marquardt equation. The results show high removal percentages, and the behavior of the experimental data is assumed to fit the LH-HW equation. The analysis of the organic intermediates by solid phase micro-extraction (SPE), HPLC and gas chromatography (CG-MS); shows that the transformation is feasible under the formation of nitro-aromatic derivatives and hydroxylated species.